2005
DOI: 10.1089/ten.2005.11.1618
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Enhances Periodontal Tissue Regeneration

Abstract: To address whether brain-derived neurotrophic factor (BDNF) could be involved in periodontal tissue regeneration, we examined the effects of BDNF on proliferation and the expression of bone (cementum)- related proteins (osteopontin, bone morphogenetic protein [BMP]-2, type I collagen, alkaline phosphatase [ALPase], and osteocalcin) in cultures of human periodontal ligament (HPL) cells, which are thought to be prerequisite for periodontal tissue regeneration, and on proliferation and angiogenesis in human endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
104
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 45 publications
12
104
1
Order By: Relevance
“…Our previous study has shown that many new blood vessels developed in BDNFinduced regenerated areas of periodontal tissue (Takeda et al, 2005). Since angiogenesis is a key phenomenon for tissue regeneration, the effect of BDNF on endothelial cell function should be clarified.…”
mentioning
confidence: 99%
“…Our previous study has shown that many new blood vessels developed in BDNFinduced regenerated areas of periodontal tissue (Takeda et al, 2005). Since angiogenesis is a key phenomenon for tissue regeneration, the effect of BDNF on endothelial cell function should be clarified.…”
mentioning
confidence: 99%
“…Various types of non-neural cells and tissue express BDNF. At the cellular level, vascular endothelial cells, osteoblastic cells, periodontal ligament cells, and immune cells express BDNF (7)(8)(9)(10)(11). At the tissue level, BDNF is expressed in tooth germ, bone, cartilage, heart, spleen, placenta, prostate, and kidney (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Its formation is key to establishing functional periodontal tissue, which is structured with newly formed cementum, alveolar bone, and connective tissue fibers inserted into these hard tissues. We have focused on using BDNF to help regenerate periodontal tissue and found that the regulation of functions of periodontal ligament cells and endothelial cells by BDNF culminates in the promotion of periodontal tissue regeneration in vitro and in vivo (10). Furthermore, cementum forms in the early stages of the regeneration stimulated by BDNF (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PDL cells have been reported to increase proliferation and the expressions of ALP and osteocalcin mRNA and osteopontin, BMP-2 and type I collagen synthesis through BDNF exposure (Tsuboi et al, 2001). Moreover, BDNF or BDNF/highmolecular-weight-hyaluronic acid reportedly increased the formation of new alveolar bone, cementum, Sharpey's fiber-like connective tissues and blood capillary in Class III furcation defects in a dog model (Takeda et al, 2005;Takeda et al, 2011).…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%